Prognostication of nonstationary temporal rows by the methods of clusterization and local approximation - Shamsha, Boris; Ajvasov, Vitalij (Видавництво Львівської політехніки, 2012)
In this paper we suggest the method of using the cluster analysis allowing the organization of clusters families and constructing local models of prognostication in every cluster.
Keywords: Forecasting; clusterization; local models